ANALISA KINERJA KEUANGAN PADA KOPERASI PEGAWAI REPUBLIK INDONESIA KANTOR URUSAN AGAMA KABUPATEN WONOGIRI PERIODE 2014-2017 - Sri Lestari; Burhanudin AY; Ida Aryati (JURNAL ILMIAH EDUNOMIKA, 2019)
The research aims to find out and describe finance performance in Koperasi Pegawai Republik Indonesia Kantor Urusan Agama Kabupaten Wonogiri period 2014-2017. This research using quantitative descriptive research. The data used in this research is secondary data are derived from the financial statements Koperasi Pegawai Republik Indonesia Kantor Urusan Agama Kabupaten Wonogiri period 2014-2017. Data analysis technique used was fiancial ratio analysis. The result show that finance performance in Koperasi Pegawai Republik Indonesia Kantor Urusan Agama Kabupaten Wonogiri period 2014-2017 based on the ratio of earning indicate the cooperatives are in less good condition. Finance performance in Koperasi Pegawai Republik Indonesia Kantor Urusan Agama Kabupaten Wonogiri period 2014-2017 based on the ratio of activities shows the cooperative is in bad condition. Finance performance in Koperasi Pegawai Republik Indonesia Kantor Urusan Agama Kabupaten Wonogiri period 2014-2017 based on liquidity ratios indicate the cooperatives are in less good condition. Finance performance in Koperasi Pegawai Republik Indonesia Kantor Urusan Agama Kabupaten Wonogiri period 2014-2017 based on solvency ratios indicate the cooperatives are in less good condition. Keywords: Finance Performance, Earning Ratio, Activity Ratio, Liquidity Ratio, Solvency Ratio